Improving overall moisture content of friction yarn for its use in foundation garments – part 2 - Pal Singh, Kanwar Varinder (2019)
As per the global scenario, physiological comfort is very basic and necessary property of the fabric. The fabrics with higher level of comfort values have a tremendous scope from the point of view of comfort in the garment industry. The comfort has been an inherent feature of the knitted textiles. To further increase the softness in knitted fabric, twistless yarns are used. As compared with that of conventional spun yarns, their strength largely depends on the amount of twist but it has the disadvantage of imparting a harsh feel to the fabric. Once the twistless yarn has been assembled in a fabric structure, the compacting forces created by the fabric structure itself hold the systems together. Hence, it is quite possible to produce a twistless knitted fabric with improved parameters of physiological comfort, which can be beneficial for apparels. An attempt has been made to develop DREF III friction spun yarn after structural modifications with an objective to analyze its feasibility for foundation garment end use by diagnosing its quantified reduction in harshness to develop foundation garments and enhancing its breathability.1 In ‘Overall Moisture Management Content’ of foundation garments; one-way transport index% is considered as the sub-function with maximum importance; as sweat or moisture is supposed to be transported from body to climate keeping its minimum conditions for desirability of comfort and handle as constant and prohibition of outer moisture to travel inside